2018
DOI: 10.1590/1413-81232018236.04682018
|View full text |Cite
|
Sign up to set email alerts
|

Dominância financeira na assistência à saúde: a ação política do capital sem limites no século XXI

Abstract: This article gives, first, a historical account of the action of capital in healthcare in contemporary Brazil and then introduces a debate on the dominance of finance ('financial dominance') in healthcare based on one case to examine: the hypertrophy of the structure for intermediation in private healthcare existing in Brazil, using the theses of José Carlos de Souza Braga as its principal reference. The article highlights the nebulous nature of what happens at the interface between the public and private elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
17

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 9 publications
1
7
0
17
Order By: Relevance
“…Added to this are new forms of financialization 39 , often related to closer links between the public and private sectors, including the government purchase of private sector services, such as the above-mentioned high-cost procedures, e.g. electroconvulsive therapy and transcranial magnetic stimulation 9 .…”
Section: The New Mental Health Policy and Counter-reformmentioning
confidence: 99%
“…Added to this are new forms of financialization 39 , often related to closer links between the public and private sectors, including the government purchase of private sector services, such as the above-mentioned high-cost procedures, e.g. electroconvulsive therapy and transcranial magnetic stimulation 9 .…”
Section: The New Mental Health Policy and Counter-reformmentioning
confidence: 99%
“…Another convergence between people of black and white race/skin color was the inexistence of basic care in the therapeutic itinerary of these people, and thus the diagnosis and referral resulted from in-hospital care. Difficulty in accessing the diagnosis was also evident, since the patients needed multiple consultations in different cities: (...) My blood pressure was 18 The lack of basic care in the itinerary implied the presence of the private sector in the search for diagnosis of black and white people. In this sense, there is a difficulty in access that is directly associated with the enormous fragmentation of care, high financial cost for correct follow-up, and low resolution in small cities: It was complicated because I spent a lot.…”
Section: Table 1 Systematization Of the Therapeutic Itinerary Of Blamentioning
confidence: 99%
“…Thus, the presence of the private sector in an important way in the therapeutic itinerary of white and black people with CRF shows that capitalism, transvested in the shape of the private service, was reorganized after the Constitution of 1988 to act in parallel with SUS: while one seeks universality, comprehensiveness and equity, the other acts to generate wealth. (18) Furthermore, the presence of the private sector demonstrates, intrinsically, how complex the process of alienating people is, since a fetishism has been created in the social imagination, regardless of race/color, which characterizes the private service as efficient, fast and problemsolving, while SUS is represented by queues at hospitals and difficult access. However, the speeches of the participants showed that, although there was the presence of the private sector in the itinerary of white and black people, black people were only diagnosed when the symptoms were evident, which shows that access to the diagnosis was more difficult for this public.…”
Section: Fragmentation Of Care and Racism Involved In The Convergencementioning
confidence: 99%
“…It should be noted that the private sector that opposed the creation of the SUS is not the same that, three decades later, competes for public resources. Currently, the private health sector is led by multi-sector financial corporations, which hold the capital not only from health plan operators, hospitals and diagnostic and therapy services, but also companies in other economic sectors 17 .…”
Section: Thirty Years Of Struggle For the Right To Health: The Conflimentioning
confidence: 99%